Integrating Band Structure Engineering with All‐Scale Hierarchical Structuring for High Thermoelectric Performance in PbTe System. Issue 3 (12th October 2016) - Pei, Yanling; Tan, Gangjian; Feng, Dan; Zheng, Lei; Tan, Qing; Xie, Xiaobing; Gong, Shengkai; Chen, Yue; Li, Jing‐Feng; He, Jiaqing; Kanatzidis, Mercouri G.; Zhao, Li‐Dong
Abstract : PbTe1− x Se x ‐2%Na‐y%SrTe system is investigated and a high maximum ZT of 2.3 at 923 K for PbTe0.85 Se0.15 ‐2%Na‐4%SrTe is reported. This is achieved by performing electronic band structures modifications as well as all‐scale hierarchical structuring and combining the two effects. It is found that high ZTs in PbTe0.85 Se0.15 ‐2%Na‐4%SrTe are possible at all temperature from 300 to 873 K with an average ZTave of 1.23. The high performance in PbTe1− x Se x ‐2%Na‐y%SrTe can be achieved by either choosing PbTe‐2Na‐4SrTe or PbTe0.85 Se0.15 ‐2Na as a matrix. At room temperature the carrier mobility shows negligible variations as SrTe fraction is increased, however the lattice thermal conductivity is significantly reduced from ≈1.1 to ≈0.82 W m −1 K −1 when 5.0% SrTe is added, correspondingly, the lattice thermal conductivity at 923 K decreases from ≈0.59 to ≈0.43 W m− 1 K −1 . The power factor maxima of PbTe1− x Se x ‐2Na‐4SrTe shift systematically to higher temperature with rising Se fractions due to bands divergence. The maximum power factors reach ≈27, ≈30, ≈31 μW cm −1 K −2 for the x = 0, 0.05, and 0.15 samples peak at 473, 573, and 623 K, respectively. The results indicate that ZT can be increased by synergistic integration of band structure engineering and all‐scale hierarchical architectures. Abstract : The PbTe1− x Se x ‐2%Na‐y%SrTe system is investigated and a high ZT of 2.3 is achieved at 923 K for PbTe0.85 Se0.15 ‐2%Na‐4%SrTe . It is found that high ZTs in PbTe0.85 Se0.15 ‐2%Na‐4%SrTe are possible at 300–873 K with an average ZTave of 1.23. The high performance can be attributed to an optimized power factor through band structures modifying and reduced lattice thermal conductivity through all‐scale hierarchical structuring and the combining the two effects.